Into the gauntlet - Haddix, Margaret Peterson (New York : Scholastic, 2010)
Throughout the hunt for the 39 Clues, Amy and Dan Cahill have uncovered history's greatest mysteries and their family's deadliest secrets. But are they ready to face the truth about the Cahills and the key to their unmatched power? After a whirlwind race that's taken them across five continents, Amy and Dan face the most the difficult challenge yet -- a task no Cahill dared to imagine. When faced with a choice that could change the future of the world, can two kids succeed where 500 years worth of famous ancestors failed?
Throughout the hunt for the 39 Clues, Amy and Dan Cahill have uncovered history's greatest mysteries and their family's deadliest secrets. But are they ready to face the truth about the Cahills and the key to their unmatched power? After a whirlwind race that's taken them across five continents, Amy and Dan face the most the difficult challenge yet -- a task no Cahill dared to imagine. When faced with a choice that could change the future of the world, can two kids succeed where 500 years worth of famous ancestors failed?
Reading level: age 9, 10, 11, and 12.
660
106376
Keywords: Brothers and sisters -- Juvenile fiction; Family secrets -- Juvenile fiction; Code and cipher stories; Family secrets -- Fiction; Ciphers -- Fiction; Mystery fiction; Family -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery fiction; Puzzles and games; Detective and mystery fiction; Code and cipher stories; Children's stories; Fiction; Juvenile works; Mystery fiction; Puzzles and games; Detective and mystery fiction